Sustainable Starch-Calotropis procera Extract Bio-Packing for Protection Against Fungus Attack and Fruit Fast Maturation - Júlia Martins Souza, Ana; Silva Rodrigues, Jordane; de Souza Bernardes, Micheli; Guerra Lima Medeiros Borsagli, Fernanda (Fine Chemical Engineering, 2023)
The proliferation of diseases in plantations, control of fruit ripening, and damages in fruits during transportation are significant agricultural concerns. Thus, this research is based on the production of a sustainable packaging film based on starch conjugated to different concentrations of natural extract from Calotropis procera seeds for agricultural applications. The films were characterized by Fourier Transform Infrared (FTIR), Nuclear Magnetic Resonance (NMR) and Surface Contact Angle. In addition, antifungal activity against Colletotrichum musae were evaluated in vitro and in vivo, as the control of fruit fast maturing were figured using banana as a model of fruit. The cytotoxicity were also analyzed. The results showed that some compounds may have an important role in this protections, as proteins, calactin and calotoxin. Moreover, it demonstrated cytocompatibility using in vitro bioassays (> 80%). The analysis of fruit fast maturing showed that the film with 50 μL·mL-1 of natural extract presented the best results, controlling the fruit ripening and protecting against diseases. Thus, for the first time, a packaging film based on starch and natural extract from Calotropis procera seed demonstrated a versatile action towards agriculture applications.